Leadership Style of Islamic School Principals and Its Impact on Organizational Communication Effectiveness: A Case Study in Indonesia - Mariska, Revi; Fatmawati, Fatmawati; Rahmawati, Rahmawati; Anti Kinas, Arni (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2023)
Leadership plays a pivotal role in the development and effectiveness of educational institutions. This study aims to explore the leadership style of a madrasah (Islamic senior high school) principal and its role in fostering effective communication within the institution. Conducted as a qualitative case study at MAN 1 Bone, Indonesia, data were collected through observations, interviews, and documentation. The findings reveal that the principal adopted a democratic leadership style characterized by inclusive decision-making, delegation of responsibilities, and regular supervision. This leadership approach significantly contributed to the development of a collaborative and communicative school environment. Effective communication, in turn, supported better coordination among teachers and staff, enhanced professional performance, and improved relationships with students' parents. The study underscores the importance of leadership style in building an open organizational climate and highlights communication as a critical tool in educational management.